Semaglutide, liraglutide and tirzepatide: Comparison of effectiveness in the treatment of obesity – a literature review - Karolina Baran; Marlena Jankowska; Natalia Jańczyk; Karolina Mędrysa; Jakub Pokrzepa; Michał Presak; Gabriela Blecharz; Julia Szwech; Alicja Winkowska; Jan Machalica (Quality in Sport)
Introduction